2016
DOI: 10.1142/s021773231650070x
|View full text |Cite
|
Sign up to set email alerts
|

Modified Fermi energy of electrons in a superhigh magnetic field

Abstract: In this paper, we investigate the electron Landau level stability and its influence on the electron Fermi energy, [Formula: see text], in the circumstance of magnetars, which are powered by magnetic field energy. In a magnetar, the Landau levels of degenerate and relativistic electrons are strongly quantized. A new quantity [Formula: see text], the electron Landau level stability coefficient is introduced. According to the requirement that [Formula: see text] decreases with increasing the magnetic field intens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 40 publications
0
22
0
1
Order By: Relevance
“…They indicated that the presence of high magnetic fields can give rise to white dwarfs of masses as high as 2.3 − 2.6M ⊙ with radii around 600 km. It is interesting to mention that Gao et al (2013) and Zhu et al (2016) made a great deal of deliberations in this direction, particularly in the study of how the Fermi energy and the electron degeneracy pressure change in a neutron star due to the presence of a strong magnetic field. Gao et al (2013) and Li et al (2016) indicated that in the presence of a strong magnetic field the electron degeneracy pressure increases with strength of the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…They indicated that the presence of high magnetic fields can give rise to white dwarfs of masses as high as 2.3 − 2.6M ⊙ with radii around 600 km. It is interesting to mention that Gao et al (2013) and Zhu et al (2016) made a great deal of deliberations in this direction, particularly in the study of how the Fermi energy and the electron degeneracy pressure change in a neutron star due to the presence of a strong magnetic field. Gao et al (2013) and Li et al (2016) indicated that in the presence of a strong magnetic field the electron degeneracy pressure increases with strength of the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al (2014)) found that both “outliers” of BH XRBs and bright AGNs follow a steeper fundamental plane of black hole activity. Coriat et al (2011) argued that the two fundamental planes are regulated by radiatively inefficient (e.g., ADAF) and radiatively efficient accretion processes (e.g., SSD + corona), respectively, if we assume the jet launching and radio radiation behave identically (see also, Deng et al 2020; Gao et al 2011a; Fu et al 2020; Li et al 2016; Zhu et al 2016; Wang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The Fermi energy of electrons inside an NS can have a direct impact not only on the weak‐interactions processes but also on the electron degeneracy pressure counteracting gravity collapse of the star. These impacts will in turn change intrinsic (e.g., Gao et al ; Liu ; Zhu et al ) EoS, internal structure, and heat evolution, and even influence the whole properties of the star. Thus, more attention has been paid to the two parameters above due to their importance.…”
Section: Introductionmentioning
confidence: 99%